2009
DOI: 10.1677/joe-08-0563
|View full text |Cite
|
Sign up to set email alerts
|

Extra-ovarian expression and activity of growth differentiation factor 9

Abstract: Growth differentiation factor 9 (GDF9) produced within the ovary plays an essential role during follicle maturation through actions on granulosa cells, but extra-ovarian expression, signalling and actions of GDF9 are less well characterised. The present studies confirm GDF9 expression in the mouse testis, pituitary gland and adrenocortical cancer (AC) cells, and establish its expression in LbT2 gonadotrophs, and in mouse adrenal glands, particularly foetal and neonatal cortical cells. AC, LbT2, TM3 Leydig and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…According to that knock-out model, ovarian GDF9 has a major influence on both LH and FSH serum levels, which does not preclude a distinct autocrine/ paracrine role of GDF9 in the pituitary. Overall, whereas the role of GDF9 in the ovary is clearly established, our work and the previous detection of GDF9 expression in rat primary pituitary cultures and L␤T2 gonadotropes (15) and in the human (41) (GEO accession GDS3834 (42)), (GEO accession GDS1096 (43)), and bovine pituitary (44) support the view that GDF9 has an important functional role in the pituitary.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…According to that knock-out model, ovarian GDF9 has a major influence on both LH and FSH serum levels, which does not preclude a distinct autocrine/ paracrine role of GDF9 in the pituitary. Overall, whereas the role of GDF9 in the ovary is clearly established, our work and the previous detection of GDF9 expression in rat primary pituitary cultures and L␤T2 gonadotropes (15) and in the human (41) (GEO accession GDS3834 (42)), (GEO accession GDS1096 (43)), and bovine pituitary (44) support the view that GDF9 has an important functional role in the pituitary.…”
Section: Discussionsupporting
confidence: 73%
“…The identification of novel secreted FSH␤ regulators might help elucidate the fundamental mechanisms underlying frequency sensitivity. Growth differentiation factor 9 (GDF9), a member of the transforming growth factor ␤ (TGF␤) superfamily that is expressed in primary pituitary cultures and gonadotrope cell lines (15), was one candidate selected for study. We found that GDF9 is a strong autocrine inducer of FSH␤ that is suppressed by GnRH and forms a network motif contributing to the GnRH frequency sensitivity of FSH␤ regulation.…”
mentioning
confidence: 99%
“…To confirm this, we assessed the ability of conditioned medium from mGDF9 or hGDF9 expressing cells to activate a phosphorylated mothers against decapentaplegic (Smad)-2/3-responsive luciferase reporter (pGRAS) in a murine adrenocortical cell line (18). Treatment of cells with mGDF9 resulted in a dose-dependent increase in luciferase activity (EC 50 28ng/ml) (Fig.…”
Section: Human Gdf9 Is Secreted In a Latent Complex With Its Prodomainmentioning
confidence: 97%
“…Wild-type and mutant hGDF9 were compared with mGDF9 for their ability to stimulate a luciferase response in a mouse adrenocortical cell line (AC) (18) or in a human granulosa cell line (KGN). Briefly, AC or KGN cells were plated in 48-well plates at 114,000 cells/well or 40,000 cells/well, respectively.…”
Section: In Vitro Bioassaymentioning
confidence: 99%
See 1 more Smart Citation